Designing the Online Collaborative Learning Using the Wikispaces - Sulisworo, Dwi (International Journal of Emerging Technologies in Learning (iJET), 2012)
Collaboration has become one of an essential skill necessary for effective functioning in society in the new era. As a consequence, the learning strategy at the higher education should consider this shifting. Web 2.0 technology is a new trend in communication technology that has become a basis of the new generation internet to make it a more mature and distinctive medium of communication. The problem is how to bring the offline learning using cooperative learning based on classroom to the online learning using this wiki. The learning design on this topic will give wide opportunity to access learning that more suitable to the new skill in the new era. Wikispaces is one of wiki facilities that operated in the web based. This wiki is so simple but suitable for collaborative learning. The learning scenario is Jig Saw approach modified to fit in the online collaborative learning environment. This technique, including two different treatments with different small groups in order to help learning and improving cooperation between students. Using this structure, students are responsible for share their skill or knowledge each other material.